Using Skills Profiling to Enable Badges and Micro-Credentials to be Incorporated into Higher Education Courses - Tom Crick (Journal of Interactive Media in Education, 2023)
Employers are increasingly selecting and developing employees based on skills rather than qualifications. Governments now have a growing focus on skilling, reskilling and upskilling the workforce through skills-based development rather than qualifications as a way of improving productivity. Both these changes are leading to a much stronger interest in digital badging and micro-credentialing that enables a more granular, skills-based development of learner-earners. This paper explores the use of an online skills profiling tool that can be used by designers, educators, researchers, employers and governments to understand how badges and micro-credentials can be incorporated within existing qualifications and how skills developed within learning can be compared and aligned to those sought in job roles. This work, and lessons learnt from the case study examples of computing-related degree programmes in the UK, also highlight exciting opportunities for educational providers to develop and accommodate personalised learning into existing formal education structures across a range of settings and contexts.